Serum IL-27 levels increase in subjects with hypothyroidism and are negatively correlated with the occurrence of nonalcoholic fatty liver disease - Wen, Yahui; Zhang, Heng; Yang, Ning; Gao, Xia; Chen, Zhe; Liu, Jia; Wang, Guang (Frontiers in Endocrinology, 2023)
Background:The level of serum interleukin-27 (IL-27) was significantly decreased in the obesity group. After injection of IL-27, obese mice showed significant weight loss,reduced fat accumulation, improved insulin resistance and hepatic steatosis.IL-27 plays a key role in the regulation of metabolic processes, but there are scarce data on circulating IL-27 levels in hypothyroidism. The purpose of this study was to assess the serum levels of IL-27 in patients with hypothyroidism and its relationship with NAFLD. Methods: 185 participants were included in this cross-sectional survey. According to thyroid function, the subjects were classified into three groups: euthyroidism (n = 55), subclinical hypothyroidism(n = 53), and hypothyroidism (n = 77).Serum IL-27 concentrations were measured by ELISA. Results: Serum IL27 levels were significantly higher in subclinical hypothyroidism and hypothyroidism groups than in the euthyroidism group.Serum IL27 levels had a negative correlation with HOMA-IR,FBG,TG, subcutaneous fat,and visceral fat, and had a positive correlation with HDL-C(P< 0.05). Furthermore, logistic regression analysis indicated that IL-27 levels, HOMA-IR, and visceral fat showed significant associations with NAFLD after complete adjustment (P< 0.05).ROC curves showed that theoptimal cut-off value of serum IL-27 for discriminating NAFLDwas 98.1pg/mL.The area under the ROC curve was 89.7% (95% CI = 0.757-0.859, p < 0.001). Conclusions: Serum IL-27 levels demonstrated a compensatory increase in patients with subclinical hypothyroidism or hypothyroidism and showed an independent association with NAFLD.These results suggested that altering the circulating levels of IL-27 may be a potential therapeutic target for NAFLD.